Participants' responsibilities in clinical research. Issue 12 (19th July 2012) - Resnik, David B; Ness, Elizabeth
Abstract : Discussions on the ethics and regulation of clinical research have a great deal to say about the responsibilities of investigators, sponsors, research institutions and institutional review boards, but very little about the responsibilities of research participants. In this article, we discuss the responsibilities of participants in clinical research. We argue that competent adult participants are responsible for complying with study requirements and fulfilling other obligations they undertake when they make an informed choice to enrol in a study. These responsibilities are based on duties related to promise-keeping, avoiding harm to one's self or others, beneficence and reciprocity. Investigators and research staff should inform participants about their responsibilities during the consent process, and should stress the importance of fulfilling study requirements. They should address any impediments to compliance, and they may provide participants with financial incentives for meeting study requirements. In very rare cases, coercive measures may be justified to prevent immanent harm to others resulting from non-compliance with study requirements.